Implementation of Good Governance and Corporate Social Responsibility (CSR) in the Development of Human Resources in MSMEs, Iwul Parung Village on 2020 - Nofiar Nofiar; Maswarni Maswarni; Nurjaya Nurjaya; Denok Sunarsi; Rofiq Noorman Haryadi (Budapest International Research and Critics University, 2022)
This study will examine the improvement of the quality of human resources, namely the implementation of good governance and Corporate Social Responsibility in the development of human resources in the environment of MSME actors, especially in Iwul Village, Bogor, Indonesia. CSR (Corporate Social Responsibility) is an activity carried out by a company for social and environmental issues, Human Resource Development is micro and macro. Human Resource Development Macro is a process of improving the quality or human ability in order to achieve development goals nation. The purpose of this study is to find out how the implementation process, Human Resource Development, and to find out the implementation of good governance and corporate social responsibility in developing human resources for SMEs that are already running. The method used is descriptive-qualitative and this research explores the role of PT. Semen Gresik (Persero) in developing human resources and small business entrepreneurs through partnership programs. The result of this training is the increasing insight and productivity level of human resources which is improving compared to before the existence of CSR.